(Business activity in Aden in the Tahiri era (858 - 923 AH / 1451 - 1517 AD - Alwajeh, Mohamed Kayed Hassan (Journal of Economic, Administrative and Legal Sciences, 2018)
The research aims at investigating the important role of Tahirian Sultans in the commercial activity in Aden during the Tahirian era. The commercial activity in Aden port was with Indian trade, the Red Sea, Hijaz, and Egypt. They could subjugate the two dangerous oppositions at that time, troops and tribes, because of their political and commercial experience. Then they practiced trade and benefited from their profits for a period of more than sixty years (1451 -1517 AD), or (858-923 AH). To achieve the objectives of this study, the researcher adopted the experimental and historical approaches to get the scientific materials related to this subject. The researcher concluded to the following findings: - The Tahirian Sultans tried hard to subjugate the troops and tribes due to their political and commercial experiences. They maintained the commercial activity of Aden port for their flexibility in dealing with the Mamluk Sultans in Egypt, their rivals who later attacked Aden and eliminated the Tahirians and ruled the whole country, Yemen.